Temporal and structural evolution of the Early Palæogene rocks of the Seychelles microcontinent - Shellnutt, J. Gregory; Yeh, Meng-Wan; Suga, Kenshi; Lee, Tung-Yi; Lee, Hao-Yang; Lin, Te-Hsien (Scientific Reports, 2017)
The Early Palæogene Silhouette/North Island volcano-plutonic complex was emplaced during the rifting of the Seychelles microcontinent from western India. The complex is thought to have been emplaced during magnetochron C28n. However, the magnetic polarities of the rocks are almost entirely reversed and inconsistent with a normal polarity. In this study we present new in situ zircon U/Pb geochronology of the different intrusive facies of the Silhouette/North Island complex in order to address the timing of emplacement and the apparent magnetic polarity dichotomy. The rocks from Silhouette yielded weighted mean 206 Pb/ 238 U ages from 62.4 ± 0.9 Ma to 63.1 ± 0.9 Ma whereas the rocks from North Island yielded slightly younger mean ages between 60.6 ± 0.7 Ma to 61.0 ± 0.8 Ma. The secular latitudinal variation from Silhouette to North Island is consistent with the anticlockwise rotation of the Seychelles microcontinent and the measured polarities. The rocks from Silhouette were emplaced across a polarity cycle (C26r-C27n-C27r) and the rocks from North Island were emplaced entirely within a magnetic reversal (C26r). Moreover, the rocks from North Island and those from the conjugate margin of India are contemporaneous and together mark the culmination of rift-related magmatism.